2008
DOI: 10.1161/circulationaha.107.732032
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines Regulate the Activity, Secretion, and Synthesis of Renalase

Abstract: Background-We previously identified renalase, a secreted novel amine oxidase that specifically degrades circulating catecholamines. Parenteral administration of either native or recombinant renalase lowers blood pressure, heart rate, and cardiac contractility by metabolizing circulating catecholamines. Renalase plasma levels are markedly reduced in patients with chronic kidney disease. It is not known whether endogenous renalase contributes to the regulation of catecholamines. Methods and Results-We show here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
213
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(225 citation statements)
references
References 23 publications
(17 reference statements)
7
213
0
5
Order By: Relevance
“…First of all, as mentioned above, renalase 1 was detected in body fluids such as blood plasma and urine [1,10,29,30]. Secondly, in patients suffering from chronic kidney disease and primary glomerulonephritis, as well as in animal model of kidney failure, extracellular renalase was absent or present at lower concentrations, indicating the kidneys as the main source of the secreted protein [1,[30][31][32].…”
Section: Renalase Isoforms and Gene Expression Patternmentioning
confidence: 99%
See 2 more Smart Citations
“…First of all, as mentioned above, renalase 1 was detected in body fluids such as blood plasma and urine [1,10,29,30]. Secondly, in patients suffering from chronic kidney disease and primary glomerulonephritis, as well as in animal model of kidney failure, extracellular renalase was absent or present at lower concentrations, indicating the kidneys as the main source of the secreted protein [1,[30][31][32].…”
Section: Renalase Isoforms and Gene Expression Patternmentioning
confidence: 99%
“…Subsequently, Desir's group proposed a catecholamine-triggered activation mechanism for circulating renalase, which would exist in inactive form under normal condition [29]. These authors reported that, while amine oxidase activity is undetectable in rat plasma under basal conditions, a 2 min infusion with epinephrine or dopamine determined the rapid (<1 min) onset of renalase activity (assayed as H 2 O 2 production specifically inhibited by an antirenalase antibody) that lasted for several minutes.…”
Section: Functional Properties Of Renalasementioning
confidence: 99%
See 1 more Smart Citation
“…According to the studies which suggested that renalase is secreted by renal cells since it was detected in both plasma and urine of healthy individuals [12,13]. Expression of renalase in peripheral nerves, adrenals, endothelium, and the central nervous system, as well as in adipose tissues, was detected both in 12.5-day-old rat embryo, and more recently, in humans [12,14]. The decrease in BP by 25% as well as a decrease in heart rate and cardiac contractility are the main actions of renalase [6].…”
Section: Introductionmentioning
confidence: 99%
“…The latter had hypertension, tachycardia, and catecholamine levels higher than the wild-type animal, therefore the knock-out mouse was reported to be more susceptible to myocardial ischemia [15]. It was also found by Li et al 2008 that renalase deficiency worsened myocardial damage during acute ischemia and the use of the recombinant renalase as treatment could ameliorate cardiac injury [12].…”
Section: Introductionmentioning
confidence: 99%